Investigation on the thermal properties of the multilayered ceramic coatings deposited using atmospheric plasma spraying. (November 2015) - Mohamed Iqbal, R.; Shabir, Mohd. F.; Dilip Jerold, B.; Mohamed Abbas, S.; Sathish, S.; Manikandan, R.; Mohamed Riswan, P.; Mohamed Raseen, I.; Mohamed Samirudeen, M. A.
Abstract : Atmospheric plasma spraying was employed to deposit Zirconia/Alumina (ZrO2 /Al2 O3 ) and Zirconia/Alumina-Titania (ZrO2 /Al2 O3 -TiO2 ) multilayer coatings with bonding material (Ni-Cr-Al) on the EN31 Mild Steel substrate. The investigation was carried out on multilayer ceramic coated specimen by thermal torch and shock test methods. The coated specimens were prepared as per ASTM standards. Micro structural analysis was carried out using scanning electron microscope to investigate the thermal resistance of the two different multilayer ceramic coatings. The results show that the multi-layered ZrO2 /Al2 O3 coating possesses improved thermal properties when compared to ZrO2 /Al2 O3 -TiO2 multilayer coating.